Efficacy and safety of Buyang Huanwu Decoction in the treatment of post-stroke depression: A systematic review and meta-analysis of 15 randomized controlled trials - Zhen, Kun; Shi, Hongshuo; Zhang, Xuecheng; Liu, Xiangyi; Li, Wenwen; Si, Guomin; Jia, Hongling; Guo, Dong (Frontiers in Neurology, 2022)
Background: Post-stroke depression is the most common neuropsychiatric disorder after stroke, which seriously affects patients' post-stroke recovery and quality of life, and is prone to recurrence of stroke and death. Buyang Huanwu Decoction is effective in treating post-stroke depression, but there is a lack of scientific systematic review and meta-analysis. Objective: To evaluate the efficacy and safety of Buyang Huanwu Decoction in treating post-stroke depression. Methods: A total of eight databases were searched by two investigators from Embase, PubMed, The Cochrane Library, Web of Science, Wanfang, CNKI, VIP, and CBM to collect randomized controlled trials that applied BHD to PSD from the time of database construction to May 2022. Data analysis was performed using Review mange5.4. Results：A total of 15 studies with 1242 patients were included. Meta-analysis showed that compared with the antidepressant drug control group, the change value of HAMD scale in the Buyang Huanwu Decoction group was significantly lower (p<0.00001, SMD=-0.85, 95%CI[-1.10,-0.28]); the total clinical effective rate was significantly increased (p<0.00001, RR=1.16, 95%CI[1.08,1.24]); neurological deficit score (p=0.0002, SMD=-1.03, 95%CI[-1.67,-0.39]), incidence of adverse reactions (p=0.02, RR=0.42, 95%CI[0.20,0.87]) and adverse reaction scale scores (p=0.00, MD=-3.58, 95%CI[-4.09,-3.08]) were significantly lower. Conclusion: Compared with antidepressants, Buyang Huanwu Decoction is more effective and safer in the treatment of post stroke depression patients. However, more high-quality studies are needed to further support the above conclusions.